Subsurface - Pinkus, Karen (Posthumanities ;, 2023)
"A highly original take on evocative terms such as extraction, burial, fossils, deep time, and speculative futurity, Subsurface questions the certainty of comfortable narrative arcs. It asks us to read literature with and against the figure of the geological column, with and against fossil fuels and the emissions warming our planet"--